Catalyst, method for producing catalyst, hydrogen generator, and fuel cell system
The use of a catalyst with layered double hydroxides and specific surface area characteristics addresses the inefficiency in hydrogen generation from boron hydride salts, achieving enhanced efficiency and stability.
Patent Information
- Application Number
- JP2023154944
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-02
AI Technical Summary
Existing methods for generating hydrogen from hydrogen storage compounds like ammonia borane are not efficient, leaving room for improvement.
A catalyst composed of layered double hydroxides with iron as the main component, interlayer anions, and interlayer water molecules, which has a BET specific surface area greater than 40 m^2/g, is used to efficiently generate hydrogen from boron hydride salts.
The catalyst significantly enhances the efficiency of hydrogen generation from boron hydride salts, maintaining stability even with repeated use, and allows for cost-effective hydrogen production at room temperature.
Smart Images

Figure 2025046703000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst, a method for producing the catalyst, a hydrogen generating device, and a fuel cell system. [Background technology]
[0002] It has been shown that a layered double hydroxide called Green Rust (GR) can generate hydrogen from a hydrogen storage compound such as ammonia borane (see Patent Document 1). However, Patent Document 1 does not fully consider how to increase the efficiency of generating hydrogen from a hydrogen storage compound, and there is room for further improvement. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2022-80364 A Summary of the Invention [Problem to be solved by the invention]
[0004] In view of the above circumstances, the present invention provides a catalyst having excellent hydrogen generation efficiency and a method for producing the same, a hydrogen generation device including the catalyst, and a fuel cell system including the hydrogen generation device. [Means for solving the problem]
[0005] According to one aspect of the present invention, there is provided a catalyst for generating hydrogen from a borohydride salt. The catalyst has an interlayer anion and an interlayer water molecule, and contains, as a main component, a layered double hydroxide containing iron. The BET specific surface area is 40 m 2 / g or more.
[0006] According to this embodiment, hydrogen can be efficiently generated from borohydride salt. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a process diagram showing one embodiment of a method for producing a catalyst of the present invention. [Diagram 2] 1 is a schematic diagram showing the configuration of one embodiment of a hydrogen generation device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present invention will be described. Various features shown in the following embodiments can be combined with each other. The catalyst of the present invention is a catalyst used to generate hydrogen from a borohydride salt. Examples of the borohydride salt include sodium borohydride, potassium borohydride, magnesium borohydride, lithium borohydride, and ammonia borane. These borohydride salts may be used alone or in combination of two or more.
[0009] This catalyst contains an iron-containing layered double hydroxide (LDH) as a main component, which has an interlayer anion and an interlayer water molecule, and is capable of efficiently generating hydrogen from a borohydride salt. In this specification, the term "main component" refers to the component that is contained in the largest amount when multiple components are contained. Components other than the "main component" are referred to as "minor components". The catalyst may consist only of the layered double hydroxide that is the main component, or may contain a minor component different from the main component.
[0010] The BET specific surface area of the catalyst is 40m 2 / g or more, and 2 / g or more 200m 2 / g or less, and 2 / g or more 180m 2 / g or less is more preferable, and 2 / g or more 160m 2 / g or less is more preferable. Thus, a catalyst having a high BET specific surface area can increase the contact area with a borohydride salt (borohydride or its ions), and therefore can further increase the efficiency of hydrogen generation from a borohydride salt. Even if the BET specific surface area of the catalyst is increased beyond the above upper limit, no further increase in effect can be expected, and it is also troublesome to manufacture a catalyst having such a large BET specific surface area. The BET specific surface area of this catalyst can be measured by the BET single-point method using nitrogen gas in accordance with JIS Z 8830:2013 "Method for measuring specific surface area of powder (solid) by gas adsorption."
[0011] The crystallite size of the layered double hydroxide is preferably about 20 nm to 70 nm, more preferably about 30 nm to 60 nm, and even more preferably about 35 nm to 50 nm. A layered double hydroxide having such a relatively large crystallite size has sufficient grain growth and is excellent in stability. Therefore, even if the catalyst is used repeatedly, the alteration, deterioration, damage, etc. can be suitably prevented. The crystallite size of this layered double hydroxide can be measured by X-ray diffraction method (XRD method).
[0012] The layered double hydroxide contains trivalent iron and divalent iron. The ratio of the number of trivalent iron atoms to the total of trivalent iron and divalent iron is preferably about 0.75 or less, more preferably about 0.4 to 0.7, and even more preferably about 0.5 to 0.6. According to the studies of the present inventors, layered double hydroxides containing a relatively large amount of divalent iron form a structure in which fine spherical particles are attached to the surfaces of columnar particles. This increases the BET specific surface area of the catalyst, and the efficiency of hydrogen generation from borohydride salt can be improved. This atomic ratio can be determined by Mossbauer spectrometry. A catalyst having the above BET specific surface area and atomic ratio can be suitably produced by the catalyst production method described below.
[0013] Examples of interlayer anions include carbonate ions, lactate ions, chloride ions, and sulfate ions. Of these, it is preferable that the interlayer anions include at least one of carbonate ions and lactate ions. These interlayer anions include boron hydride (BH3 in the case of ammonia borane) generated from borohydride salts or its ions (BH4 - It is easily exchanged with sodium borohydride, etc., and boron hydride or its ions are easily incorporated between the layers where water molecules exist. This makes it possible to further increase the efficiency of hydrogen generation through the hydrolysis reaction (reaction with water molecules) of boron hydride or its ions. The layered double hydroxide preferably has the general formula: [Fe II 1-x Fe III x (OH)2] x+ (x / n)[A n- ] x- m[H2O] (where A n- is an interlayer anion, and H2O is an interlayer water molecule.
[0014] The above-mentioned catalyst is produced by the following catalyst production method: Hereinafter, one embodiment of the catalyst production method of the present invention will be described. FIG. 1 is a process diagram showing one embodiment of the method for producing a catalyst of the present invention. The method for producing the catalyst shown in FIG. 1 includes a step of preparing raw materials containing a divalent iron salt (step S1), a step of preparing a mixed liquid by mixing the raw materials (step S2), a step of obtaining a catalyst by hydrothermal synthesis of the raw materials in the mixed liquid (step S3), a step of recovering the catalyst by removing the solvent (step S4), a step of washing the catalyst (step S5), and a step of drying the catalyst (step S6). Each step will be described below in order.
[0015] (Process S1) In this step S1, in addition to a divalent iron salt as a raw material for the catalyst, a nucleating agent and a reducing solvent are prepared. Here, various salts containing divalent iron can be used as the divalent iron salt. Among them, the divalent iron salt is preferably at least one selected from the group consisting of FeCl2, Fe(NO3)2, FeSO4, and Fe(CH3COO)2. By using such a divalent iron salt, it is easy to produce a layered double hydroxide (catalyst) that is stable and does not deteriorate over time. In addition, according to the inventors' investigation, the BET specific surface area of the catalyst tends to be large, although the reason is unclear. The divalent iron salt is preferably a hydrate. By using such a divalent iron salt, it is easy to produce a layered double hydroxide (catalyst) having the above-mentioned properties.
[0016] The nucleating agent is not particularly limited, but it is preferable to use at least one selected from the group consisting of sodium acetate (CH3COONa), potassium acetate (CH3COOK), and sodium acetate trihydrate (CH3COONa 3H2O). By using such a nucleating agent, it is easy to produce a layered double hydroxide (catalyst) that is stable and does not deteriorate over time. The reducing solvent is not particularly limited, but it is preferable to use, for example, glycerol or ethylene glycol. By using these reducing solvents, lactate ions can be easily introduced as interlayer anions into the layered double hydroxide. The reducing solvent may contain water. The mixing ratio of the divalent iron salt to the nucleating agent is preferably about 100:50 to 100:500 in terms of molar ratio, more preferably about 100:100 to 100:400, and even more preferably about 100:150 to 100:300. In this case, the layered double hydroxide (catalyst) can be produced smoothly and reliably.
[0017] (Process S2) In this step S2, the divalent iron salt, the nucleating agent, and the reducing solvent are mixed substantially simultaneously to prepare a mixed solution. When the divalent iron salt and the nucleating agent are mixed separately into the solvent, pre-heating is required before the hydrothermal synthesis. However, since the divalent iron salt and the nucleating agent are mixed into the solvent at once, the hydrothermal synthesis can be performed without pre-heating, and therefore the number of steps can be reduced. In addition, since the divalent iron salt and the nucleating agent are not dissolved but are in a suspended state in the mixed liquid, the mixed liquid is also called a suspension. (Process S3) In this step S3, the raw materials are reacted in the mixed liquid by hydrothermal synthesis to obtain a catalyst. Here, the hydrothermal synthesis is preferably carried out in a state where the mixed liquid is contained in a sealed container. In this case, it is possible to prevent oxygen from being continuously supplied to the mixed liquid from the external environment. As a result, it is possible to reduce the amount of divalent iron that is oxidized and converted to trivalent iron. This makes it possible to make the catalyst particles finer, increase the BET specific surface area, and also increase the amount of divalent iron contained in the catalyst.
[0018] The temperature in the hydrothermal synthesis is preferably about 50° C. or higher and about 350° C. or lower, more preferably about 150° C. or higher and about 250° C. or lower, and even more preferably about 150° C. or higher and 250° C. or lower. By carrying out the hydrothermal synthesis within such a temperature range, it is possible to efficiently produce a layered double hydroxide (catalyst), and to prevent structural changes in the layered double hydroxide and alteration and deterioration of the solvent, thereby producing a high-quality layered double hydroxide. The time for the hydrothermal synthesis is preferably about 0.5 to 50 hours, more preferably about 1 to 40 hours, and even more preferably about 1.5 to 30 hours. By carrying out the hydrothermal synthesis within such a time range, a sufficient amount of layered double hydroxide (catalyst) can be produced.
[0019] (Process S4) In this step S4, the solvent is removed from the mixed liquid after the hydrothermal synthesis to recover the catalyst. The solvent can be removed by, for example, filtration, suction filtration, decantation, centrifugation, or the like. (Process S5) In this step S5, the recovered catalyst is washed with a washing liquid. Examples of the cleaning liquid include water (distilled water, ultrapure water, RO water, etc.), alcohols (ethanol, etc.), ketones (acetone, etc.), etc. These may be used alone or in combination of two or more. (Process S6) In this step S6, the catalyst is dried. The catalyst can be suitably dried by, for example, natural drying, heat drying, blow drying, vacuum drying, or the like.
[0020] Next, an embodiment of the hydrogen generating device of the present invention will be described. The hydrogen generating device includes a catalyst and a borohydride salt. FIG. 2 is a schematic diagram showing the configuration of one embodiment of the hydrogen generation device of the present invention. The hydrogen generation device 1 shown in Fig. 2 has a bottomed cylindrical container 2. A partition wall 3 is provided midway in the height direction of the container 2, and the space within the container 2 is divided into an upper space 2a and a lower space 2b. In the upper space 2a, a solid borohydride salt is accommodated on the partition wall 3. In addition, in the lower space 2b, a mixture of a catalyst and water is accommodated. A lid 4 is attached to the container 2 so as to close the upper opening, and a piston 5 is disposed on the borohydride salt contained in the upper space 2a.
[0021] A compressed spring (biasing member) 6 is disposed between the lid 4 and the piston 5. As a result, the borohydride salt is biased (pressed) downward by the piston 5. The vessel 2 is provided with an injection port 21 communicating with the upper space 2a and an exhaust gas port 22 communicating with the lower space 2b. In addition, a discharge port 31 communicating with the upper space 2a is provided in the center of the partition wall 3. The injection port 21 and the lower space 2b are connected by a line L, and a filter (not shown) and a pump P are provided in this line L in this order from the lower space 2b side.
[0022] According to this configuration, when the water in the mixed liquid is supplied from the lower space 2b to the upper space 2a via the line L and the injection port 21 by operating the pump P, the borohydride salt dissolves in the water. The water in which the borohydride salt is dissolved is returned to the lower space 2b through the exhaust port 31 and supplied to the mixed liquid. As a result, hydrogen is generated from borohydride or its ions due to the action of the catalyst in the mixed liquid. The generated hydrogen is exhausted from the hydrogen generation device 1 through the exhaust gas port 22. The reaction between the borohydride salt and the catalyst is sufficiently promoted by irradiation with sunlight, but a light source may be provided on the outer periphery of the container 2 to irradiate the mixed liquid contained in the lower space 2b with light of a specific frequency wavelength.
[0023] In addition, the reaction between the borohydride salt and the catalyst proceeds sufficiently even at room temperature (25° C.), which has the advantage that hydrogen can be generated from the borohydride salt at low cost. The fuel cell system of the present invention is provided by combining such a hydrogen generation device 1 with a fuel cell. That is, one embodiment of the fuel cell system of the present invention includes the hydrogen generation device 1 and a fuel cell that generates power by using hydrogen generated in the hydrogen generation device 1. The catalyst, the method for producing a catalyst, the hydrogen generation device, and the fuel cell system of the present invention have been described above, but the catalyst, the method for producing a catalyst, the hydrogen generation device, and the fuel cell system of the present invention are not limited to the above-described embodiments. Furthermore, it may be provided in the following aspects:
[0024] (1) A catalyst used to generate hydrogen from borohydride salts, which has interlayer anions and interlayer water molecules, contains an iron-containing layered double hydroxide as a main component, and has a BET specific surface area of 40 m 2 / g or more of a catalyst.
[0025] (2) The catalyst according to the above (1), wherein the crystallite size of the layered double hydroxide is 20 nm or more and 70 nm or less.
[0026] (3) The catalyst according to the above (1) or (2), wherein the layered double hydroxide contains trivalent iron and divalent iron, and the atomic ratio of the trivalent iron to the sum of the trivalent iron and the divalent iron is 0.75 or less.
[0027] (4) The catalyst according to any one of the above (1) to (3), wherein the interlayer anion includes at least one of a carbonate ion and a lactate ion.
[0028] (5) A method for producing the catalyst according to any one of (1) to (4) above, comprising the steps of: preparing raw materials containing a divalent iron salt; preparing a mixed solution by mixing the raw materials; and obtaining the catalyst by hydrothermal synthesis of the raw materials in the mixed solution.
[0029] (6) The method for producing a catalyst according to the above (5), wherein the hydrothermal synthesis is carried out in a state where the mixed liquid is contained in a sealed container.
[0030] (7) The method for producing a catalyst according to the above (5) or (6), wherein the temperature in the hydrothermal synthesis is 50° C. or higher and 350° C. or lower.
[0031] (8) The method for producing a catalyst according to any one of the above (5) to (7), wherein the time for the hydrothermal synthesis is from 0.5 hours to 50 hours.
[0032] (9) The method for producing a catalyst according to any one of (5) to (8) above, wherein the divalent iron salt is at least one selected from the group consisting of FeCl2, Fe(NO3)2, FeSO4 and Fe(CH3COO)2.
[0033] (10) The method for producing a catalyst according to the above (9), wherein the divalent iron salt is a hydrate.
[0034] (11) A hydrogen generating device comprising the catalyst according to any one of (1) to (4) above and a borohydride salt.
[0035] (12) A fuel cell system comprising: the hydrogen generation device according to (11) above; and a fuel cell that generates electricity using hydrogen generated by the hydrogen generation device. Of course, this is not the case.
[0036] Finally, although various embodiments according to the present disclosure have been described, these are presented as examples and are not intended to limit the scope of the invention. The novel embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. The embodiments and their modifications are included within the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. EXAMPLES
[0037] The present invention will be described in more detail below using the following examples and comparative examples, but the present invention is not limited to the following examples.
[0038] 1. Catalyst Preparation Example 1 First, 1 mol of FeCl2·4H2O (iron salt), 3 mol of sodium acetate (nucleating agent), and 82 mol of glycerol (reducing solvent) were prepared. Next, these were put into a sealed polytetrafluoroethylene container and mixed to obtain a mixed solution. Note that FeCl2·4H2O was ground in a mortar before use.
[0039] The container was kept sealed, and the mixture was heated at 200°C for 24 hours. As a result, layered double hydroxide (catalyst) was obtained by hydrothermal synthesis of FeCl2·4H2O and sodium acetate in the mixture. Thereafter, the mixture after the hydrothermal synthesis was centrifuged to recover the catalyst. Next, the recovered catalyst was washed twice with 20 mL of ethanol, once with 20 mL of a washing solution prepared by mixing pure water and ethanol at a volume ratio of 1:1, and once with 20 mL of ethanol. Finally, the washed catalyst was dried at 80° C. for 24 hours. Through the above steps, the catalyst of Example 1 was obtained.
[0040] Example 2 The catalyst of Example 2 was produced in the same manner as in Example 1, except that the recovered catalyst was washed four times with 20 mL of ethanol and then dried by vacuum drying. Example 3 A catalyst of Example 3 was produced in the same manner as in Example 1, except that the washed catalyst was dried by vacuum drying.
[0041] Example 4 A catalyst of Example 4 was produced in the same manner as in Example 1, except that the mixed liquid was heated at 100°C. Example 5 The catalyst of Example 5 was produced in the same manner as in Example 1, except that the mixed liquid was heated at 150°C.
[0042] Example 6 The catalyst of Example 6 was produced in the same manner as in Example 1, except that the mixed liquid was heated for 12 hours. Example 7 The catalyst of Example 7 was produced in the same manner as in Example 1, except that the mixed liquid was heated for 6 hours.
[0043] (Comparative Example) First, 3 moles of sodium acetate (nucleating agent) and 82 moles of glycerol (reducing solvent) were added to a glass beaker. Next, the above components were heated in a glass beaker at 80° C. for 30 minutes, thereby mixing sodium acetate with glycerol to prepare a mixed solution. Next, 0.25 mol of FeCl3·6H2O (iron salt) and 0.75 mol of FeCl2·4H2O (iron salt) were added to the mixture and heated at 80°C for 90 minutes, resulting in the mixture of FeCl3·6H2O and FeCl2·4H2O with the glycerol. Thereafter, the same procedure as in Example 1 was carried out to produce a comparative catalyst.
[0044] 2. Measurement and Evaluation 2-1.BET specific surface area The catalysts obtained in each of the Examples and Comparative Examples were subjected to measurement of the BET specific surface area in accordance with JIS Z 8830:2013 "Method for measuring the specific surface area of powder (solid) by gas adsorption." The BET specific surface areas are shown in Tables 1 and 2 below.
[0045] 2-2.XRD measurement The catalysts obtained in each of the Examples and Comparative Examples were subjected to XRD measurement using an XRD measuring device (manufactured by Rigaku Corporation, "Ulitima IV"). The crystallite sizes calculated based on the full width at half maximum of the peaks observed in this XRD measurement are shown in Tables 1 and 2.
[0046] 2-3. Measurement of the atomic ratio of iron The catalysts (layered double hydroxides) obtained in each of the Examples and Comparative Examples were subjected to Mössbauer spectroscopy. 57 The Mössbauer spectrum of Fe was measured. The atomic ratio of trivalent iron to the total of trivalent iron and divalent iron estimated by this Mössbauer spectroscopy is shown in Tables 1 and 2.
[0047] 2-4.SEM photography The catalysts obtained in each of the Examples and Comparative Examples were photographed using a scanning electron microscope (manufactured by JEOL, "JSM-7001F / SHL") at a magnification of 30,000 times to obtain SEM images. The SEM images are shown in Tables 1 and 2.
[0048] 2-5. Hydrogen generation test First, 15 mg of the catalyst obtained in each of the Examples and Comparative Examples, 5 mL of a 20 mass % aqueous glycerol solution, and 20 μmol of ammonia borane were placed in a test tube and mixed. Next, the test tube was placed in an environment where the mixture in the test tube was irradiated with artificial sunlight (solar simulator). The amount of hydrogen generated during the 120 minutes from the start of the standing was measured. The amount of hydrogen generated was measured by gas chromatography. When no catalyst was used, almost no hydrogen was generated, and the amount of hydrogen generated was substantially 0 μmol. The results are also shown in Tables 1 and 2.
[0049] [Table 1]
[0050] [Table 2]
[0051] As shown in the SEM images in Tables 1 and 2, the catalysts of the examples formed a structure in which fine spherical particles were attached to the surfaces of columnar particles, whereas the catalysts of the comparative examples formed a structure of columnar particles with no fine spherical particles attached to the surfaces. It was also confirmed that the amount of hydrogen generated could be changed by adjusting the BET specific surface area. [Explanation of symbols]
[0052] 1: Hydrogen generator 2: Container 2a: Upper space 2b: Lower space 21: Injection port 22: Exhaust gas port 3: Bulkhead 31: Discharge port 4: Lid 5: Piston 6: Spring L: Line P: Pump S1: Process S2: Process S3: Process S4: Process S5: Process S6: Process
Claims
1. A catalyst for use in generating hydrogen from a borohydride salt, comprising: The present invention has an interlayer anion and an interlayer water molecule, and contains an iron-containing layered double hydroxide as a main component. BET specific surface area is 40m 2 / g or more.
2. The catalyst according to claim 1, A catalyst, wherein the crystallite size of the layered double hydroxide is 20 nm or more and 70 nm or less.
3. The catalyst according to claim 1, The layered double hydroxide contains trivalent iron and divalent iron, A catalyst, wherein the atomic ratio of the trivalent iron to the sum of the trivalent iron and the divalent iron is 0.75 or less.
4. The catalyst according to claim 1, The interlayer anion comprises at least one of a carbonate ion and a lactate ion.
5. A method for producing the catalyst according to any one of claims 1 to 4, comprising the steps of: Providing a raw material containing a divalent iron salt; A step of preparing a mixed liquid by mixing the raw materials; and obtaining the catalyst by hydrothermal synthesis of the raw materials in the mixed liquid.
6. The method for producing a catalyst according to claim 5, The hydrothermal synthesis is carried out in a state where the mixed liquid is contained in a sealed container.
7. The method for producing a catalyst according to claim 5, The method for producing a catalyst, wherein the temperature in the hydrothermal synthesis is 50° C. or higher and 350° C. or lower.
8. The method for producing a catalyst according to claim 5, The method for producing a catalyst, wherein the hydrothermal synthesis time is 0.5 hours or more and 50 hours or less.
9. The method for producing a catalyst according to claim 5, The divalent iron salt is FeCl 2 , Fe(NO 3 ) 2 , FeSO 4 and Fe(CH 3 COO) 2 The method for producing a catalyst, wherein the catalyst is at least one selected from the group consisting of:
10. The method for producing a catalyst according to claim 9, The method for producing a catalyst, wherein the divalent iron salt is a hydrate.
11. 1. A hydrogen generating apparatus comprising: The catalyst according to any one of claims 1 to 4, and a borohydride salt.
12. 1. A fuel cell system comprising: The hydrogen generating apparatus according to claim 11 ; a fuel cell that generates electricity using the hydrogen generated in the hydrogen generation device.
Citation Information
Patent Citations
Green rust, production method thereof, pigment, and anion exchanger
JP2022080364A